Diversidade de acessos de maxixe (cucumis anguria l.) do nortenordeste brasileiro - Silva, Ricardo Alexandre Moraes da (2017)
The objective of the present work was to study the genetic diversity of gherkin accessions by morpho-agronomic characters, physical-chemical characters and ISSR markers. Thirty-eight accessions and two cultivars (Maxixe do Norte and Calcutá) were evaluated in a randomized block design with three replicates in Mossoró. Nineteen accessions came from the North Region and nineteen came from the Northeast Region of Brazil. The morphological characterization was done with fifteen morpho-agronomic characters, six physicochemical characters and four characters related to bioactive compounds and antioxidants, while nine ISSR markers were used in the molecular analysis. The clustering of the accessions was done by the UPGMA hierarchical technique using the Mahalanobis distance as a measure of dissimilarity for quantitative data (morpho-agronomics, physicochemical and active compounds) and the complement of the Jaccard Index for molecular data. The main components technique was used for morpho-agronomic and physicochemical analysis. In the study of molecular diversity, we estimated the percentage of polymorphic loci, the diversity index of Shannon, the heterozygosity, and GST coefficient. It was possible to separate the accessions according to their origin when the morpho-agronomic and physical-chemical characters were used together, as well as when only those related to bioactive compounds and antioxidants were evaluated. The ascorbic acid, with 75.88%, and the average fruit weight with 18.63% were the characteristics that contributed most to the genetic divergence. It was not possible to separate the accessions for their origin in the molecular analysis with ISSR markers. The greatest molecular differentiation was found within the populations. There is no association between the diversity in accessions based on ISSR markers and phenotypic data of morpho-agronomic and biochemical characters. There is variability in the gherkin accesses of the North and Northeast Regions of Brazil for morpho-agronomic, biochemical and ISSR markers. This variation must be conserved because it presents potential for use in genetic improvement work